Composite sliding part and manufacturing method thereof
By forming a Zn-Fe alloy layer on the surface of the iron-based material and combining a high-strength bronze alloy layer with this alloy layer, the form of the brittle intermetallic compound is converted into a complex three-dimensional alloy phase, solving the problem of low bonding strength in the prior art, achieving high strength and good wear and seizure resistance.
Patent Information
- Application Number
- JP2021108311
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-30
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2041-06-30
AI Technical Summary
The prior art When combining high-strength bronze alloys with iron-based materials, it is easy to form a brittle FeAl or FeSi interphase metal compound film, resulting in a decrease in bonding strength and making it difficult to apply to actual components that need to be processed.
By galvanizing the surface of the iron-based material, a Zn-Fe alloy layer is formed, and a high-strength bronze alloy layer is combined with this alloy layer, and the form of the brittle intermetallic compound is converted into a complex three-dimensional alloy phase and a copper alloy phase, thereby improving the bonding strength.
It effectively improves the bonding strength of iron-based materials and high-strength bronze alloys, reduces the formation of brittle intermetallic compounds, improves the wear and seizure resistance of components.
Smart Images

Figure 0007649009000001 
Figure 0007649009000002 
Figure 0007649009000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an iron-copper composite sliding part in which a high-strength brass alloy layer excellent in wear resistance and seizure resistance is formed on the sliding surface of an iron-based material, and to a method for producing the same. [Background technology]
[0002] Conventionally, JIS H3250 high strength brass rods have been used for bearing materials for high load applications and sliding parts such as the swash plates and piston shoes of axial piston pumps because they require high fatigue strength, wear resistance, and seizure resistance to withstand repeated loads. However, in recent high speed and high pressure hydraulic pumps, the strength of these rods is insufficient, so composite sliding components made by bonding a tough iron-based material with a wear-resistant high strength brass alloy that has excellent friction and wear characteristics are used (Patent Document 1). The wear-resistant high-strength brass alloys used in sliding parts such as the swash plates and piston shoes of hydraulic piston pumps are made by adding aluminum and silicon to JIS high-strength brass to precipitate high-hardness manganese silicide (Mn5Si3).
[0003] Conventionally, when joining a wear-resistant high-strength brass alloy to a ferrous material, one of the following methods has been used. 1) Brazing 2) Overlay welding 3) Casting dolls 4) Thermal spraying 5) Sintering 6) Diffusion bonding using phosphorus bronze or nickel insert materials The above-mentioned bonding methods have problems such as technical difficulties, being costly and unsuitable for mass production, and low bonding strength.
[0004] Patent Document 1 discloses a method for joining an iron-based material and a wear-resistant high-strength brass alloy. In the joining method of Patent Document 1, no insert material is used, and the iron-based material is heated while covered with flux or while being blocked from oxygen by a method such as a vacuum, and the high-temperature iron-based material and the molten high-strength brass alloy are brought into direct contact with each other, and then rapidly cooled by shower water cooling, thereby suppressing the formation of a compound layer at the joining interface and joining the materials. However, when high-temperature iron-based materials are cooled with shower water, they undergo martensitic transformation and become hardened to a high hardness, so when machining high-strength brass alloys after joining, tempering at around 600°C is essential. However, alloying elements such as Al and Si, which have a high affinity with iron, form a compound layer with the iron during tempering, which significantly reduces the bonding strength, making it extremely difficult to apply this to actual parts that require machining. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 11-58034 Summary of the Invention [Problem to be solved by the invention]
[0006] Casting welding, in which a molten brass alloy is brought into direct contact with a hot ferrous material covered with flux, is a relatively easy joining method for ordinary brass. However, in the case of wear-resistant high-strength brass alloys with added aluminum or silicon, there is a problem in that a brittle intermetallic compound film of FeAl or FeSi is formed at the joining interface, which significantly reduces the joining strength. The challenge is to obtain high joining strength with iron-based materials without generating this brittle intermetallic compound film. SUMMARY OF THE PRESENT EMBODIMENTS Accordingly, an object of the present invention is to provide a composite sliding part having excellent bonding strength between an iron-based material and a high-strength brass alloy, and a method for manufacturing the same. [Means for solving the problem]
[0007] The composite sliding component according to the present invention is characterized by having a main body made of an iron-based material, a Zn-Fe-based alloy layer formed on a surface of the main body, and a high-strength brass alloy layer having excellent wear resistance and seizure resistance bonded to the surface of the alloy layer. In this way, the brittle FeAl or FeSi-based film-like intermetallic compounds that are generated in the conventional casting deposition process are transformed into a three-dimensionally intricate composite form of the intermetallic compound and copper alloy in the present invention, improving brittleness, and a composite sliding part made of an iron-based material with high bonding strength and wear-resistant high-strength brass is obtained.
[0008] An example of a piston shoe to which the present invention is applied is shown in FIG. A wear-resistant high-strength brass alloy 2 containing manganese and silicon is fusion-bonded to the sliding surface of the shoe body 1, which is made of chrome-molybdenum steel with high fatigue resistance. In addition, the metal structure of the bonding interface has a bonding layer in which the FeSi-based columnar intermetallic compound and the copper alloy are three-dimensionally interwoven. The shoe body 1 is rotatably accommodated in the accommodating recess 31 formed in the first end 51 of the piston 5 with the spherical portion 12 and is joined by crimping. The shoe body 1 slides on the swash plate 4 at a high speed of 10 m / s while receiving the reaction force of the piston discharge of 40 MPa. The shoe surface is lubricated by introducing part of the piston oil pressure through first through hole 3 and second through hole 32 provided in the center of the piston and sealing it with annular protrusion 21, thereby maintaining oil pressure balance on the piston shoe surface.
[0009] Axial piston pump shoes are required to have good sliding properties and wear resistance under high pressure when paired with a high-hardness carburized steel swash plate. For this reason, high-strength brass alloys containing added elements such as Al, Mn, Si and Ni are preferable. However, the inventors' investigations have revealed that when such molten copper alloys are directly brought into contact with high-temperature ferrous materials and welded using high-pressure air cooling to prevent martensitic transformation, brittle film-like precipitates such as Fe-Si-Mn compounds are generated on the joining surface, causing peeling defects on the joining surface and significantly reducing the joining strength. In addition, Al also has a high affinity with Fe, and it is known that a brittle Al-Fe intermetallic compound layer precipitates on the joining surface.
[0010] In the present invention, it was found that when a zinc plating is applied to the surface of an iron-based material, zinc dissolves into the copper alloy upon contact with the molten copper alloy, the solute concentration gradient increases in the vicinity of the contact surface, and brittle intermetallic compounds solidify and grow not in the form of a film but as columnar crystals. Details will be given later, but Figure 2(a) shows a ferrous base material that has been molten zinc plated and then brought into contact with molten high-strength brass, while Figure 2(b) shows a product that has been electroplated with Cu instead of molten zinc plating. In order to generate a concentration gradient sufficient for columnar crystal growth, the thickness of the zinc plating is preferably 15 microns or more. For example, in hot-dip galvanizing, a zinc plating with a large thickness can be easily obtained. However, if the zinc film is too thick, the zinc equivalent of the brass alloy in the vicinity of the contact surface becomes too high, causing δ-copper to crystallize and reducing the bonding strength, so it is preferable that the zinc plating be 300 microns or less.
[0011] By making the surface of the iron base material, which forms the joining interface, into a Zn-Fe alloy layer, the surface area of the iron that acts as the heterogeneous solidification nucleus for the Fe-Si compounds is reduced, and the spacing between the Fe-Si compounds that grow into columnar crystals becomes sparse. A composite of metal and compound, in which the gaps between the columnar crystals are filled with copper alloy, significantly improves the brittleness of the intermetallic compound formed at the bonding interface, resulting in high bonding strength.
[0012] On the other hand, in hot-dip galvanizing, zinc diffuses into the iron base during the plating process to form a Zn-Fe alloy layer. In particular, the thickness of the alloy layer can be increased by allowing the steel to cool after hot-dip galvanization. The Zn-Fe alloy layer can also be obtained by subjecting the material to heat treatment at 350°C to 500°C after electrolytic zinc plating, but can also be obtained by heating the material to a temperature at which the flux melts (800°C or higher) in the welding process. The composition of the Zn-Fe alloy layer, called the ζ layer, is FeZn 13 It is presumed to be an alloy layer of iron and zinc with relatively low bonding strength. When zinc comes into contact with molten copper alloy and dissolves into the copper alloy, an iron skeleton is left behind, and the copper alloy wets and penetrates into this void, forming a bonding layer in which the iron and copper alloy are three-dimensionally intertwined. FIG. 3(a) shows an enlarged photograph of the joint in FIG. 2(a), and FIG. 3(b) shows a Cu-Kα analysis (distribution) image. This bonding layer significantly improves the bonding strength and enhances the bonding quality between the ferrous material and the high-strength brass alloy. Effect of the Invention
[0013] When a molten high-strength brass alloy is brought into direct contact with a high-temperature ferrous material, it is unavoidable that a fragile intermetallic compound will form between the alloying elements Al, Si, etc., which have a high affinity with the iron that has dissolved from the contact surface. The film-like formation of this intermetallic compound significantly reduces the joint strength. The sliding component according to the present invention changes the intermetallic compound formed at the bonding surface into a composite of the copper alloy and the compound, and forms a bonding layer in which the iron and copper alloy are three-dimensionally interwoven, resulting in excellent bonding quality. [Brief description of the drawings]
[0014] [Figure 1] A cross-sectional view of a shoe of an axial piston pump to which the present invention is applied is shown. A high-strength brass alloy layer is formed on the sliding surface between the body and the swash plate. [Diagram 2] A structural photograph showing the morphology of the intermetallic compounds formed at the bonding interface. a) is a bonding surface where high strength brass was cast and welded directly onto the surface of an iron-based material, and b) is a bonding surface where high strength brass was cast and welded onto an iron-based material using the present invention. A change in the morphology of the intermetallic compounds formed at the bonding interface can be seen. [Diagram 3] Scanning electron microscope photographs showing a bonding layer in which copper alloy is three-dimensionally intertwined: a) is an enlarged photograph of the compound layer and bonding layer, and b) is the copper distribution in the same field of view. The compound layer forms a complex with the copper, and a bonding layer in which iron and copper are three-dimensionally intertwined with the iron base underneath can be seen. [Figure 4] A diagram showing the manufacturing method of cast welding [Diagram 5] Table showing the components of the high strength brass alloy used in this embodiment [Figure 6] Diagram showing the shear test method [Figure 7] Table showing the evaluation results of weldability DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] When molten high-strength brass containing aluminum or silicon is brought into contact with high-temperature iron-based materials that have been covered with a conventional flux such as borax and heated to prevent oxidation in the air, reducing atmosphere, or vacuum, a brittle iron-based compound layer is formed on the contact surface with the molten metal, resulting in low joint strength and easy peeling during use of the sliding parts. The compound layer is in the form of a film, and is formed by a diffusion reaction during the cooling process after the brass alloy solidifies. Conventionally, there have been attempts to suppress the diffusion of iron by plating with copper or nickel, but the plating dissolves immediately when it comes into contact with the molten brass alloy, and it is not possible to suppress the formation of compounds during the cooling process after the brass alloy solidifies. Therefore, in joining high-strength brass and iron-based materials, composite sliding parts are manufactured by using methods such as brazing without melting the copper alloy and without directly contacting high-temperature iron with the copper alloy. In contrast, the present invention is based on a new concept of improving bondability by changing the form of the compounds that are generated, rather than suppressing the generation of compounds during cast welding.
[0016] The amount of silicon and manganese contained in the high-strength brass alloy is related to the thickness of the compound layer formed with the iron-based material, and in the practice of the present invention, the components of the high-strength brass alloy are as follows, all in mass %, Mn: 2.0-5.0%, Si: 0.5-2.0%, to provide a strong bond with the iron-based material. Manganese combines with silicon to form needle-shaped intermetallic compounds of Mn5Si3 in the metal structure, improving the wear resistance and seizure resistance of high-strength brass alloys. If the manganese content is less than 2.0%, sufficient acicular intermetallic compounds are not obtained to improve wear resistance, and if it is more than 5.0%, a brittle intermetallic compound layer is formed at the joint, reducing the joint strength. Furthermore, if the silicon content is less than 0.5%, sufficient acicular intermetallic compounds are not obtained to improve wear resistance, and if it is more than 2.0%, a brittle intermetallic compound layer is formed at the joint, reducing the joint strength.
[0017] In order to obtain the properties required for the high strength brass alloy to be welded to the composite sliding parts, the reasons for selecting the other elements to be added to this high strength brass alloy and the limit ranges of the amounts of the other elements to be added are as follows. Cu: 55.0-65.0% Copper is the main component of the alloy, and if it is more than 65.0%, the tensile strength, hardness, and wear resistance required for a high-strength brass alloy cannot be obtained. Also, if it is less than 55.0%, the zinc equivalent of the brass alloy is too large, so elongation decreases and toughness is insufficient. Preferably, Cu: 58.0 to 63.0%. Al: 0.5-2.0% In the present invention, Al is not an essential component, but Al dissolves in copper to increase the tensile strength and hardness of the brass alloy. If it is less than 0.5%, the effect is low, and if it is more than 2.0%, a brittle intermetallic compound layer is formed in the joint, reducing the joint strength. Pb: 0.5-4.0% In the present invention, Pb is not an essential component, but lead improves the machinability and seizure resistance of the brass alloy. On the other hand, it is designated as an environmentally hazardous element by the RoHS Directive and other directives, and its addition must be kept to a small amount. However, if it is less than 0.5%, the effect is low. Currently, the RoHS Directive allows less than 4.0% lead in copper alloys. Sn: 1.0% or less In the present invention, Sn is not an essential component, but even a small amount of Sn prevents dezincification corrosion of high strength brass. However, if the Sn content is 1% or more, the Cu4Sn phase appears and embrittles the brass alloy, so the content must be 1.0% or less. P:0.1% or less In the present invention, P is not an essential component. However, since a molten metal to which P is added does not contain slag and has high fluidity, it has the effect of facilitating the floating and removal of the flux used during joining. However, if its content exceeds 0.1%, the brass alloy becomes hard and air bubbles tend to form, so the content is set to 0.1% or less. Zn: remainder Zinc, together with copper, is the main component of the alloy, and determines the tensile strength, hardness, and wear resistance of the high-strength brass alloy. The amount of zinc in the alloy is controlled by the amount of copper.
[0018] Next, pre-welding treatment of iron-based materials, which is performed to improve the joining strength, will be described. A zinc layer of 15 μm or more is formed on the joining surfaces of ferrous materials by an appropriate method such as hot-dip plating, electroplating, or metal spraying. If the thickness of the zinc layer is insufficient, the solute concentration gradient at the bonding interface does not become large, and no morphological change occurs in the film-like compound layer. In the case of the hot-dip galvanizing method, an alloy layer with zinc is formed when the zinc layer is formed, but if the zinc layer is formed by a method other than the hot-dip galvanizing method, a heat treatment is performed at 350 to 500°C for 30 minutes or more to form an alloy layer with zinc on the iron surface. The alloy layer formed at this time is an alloy layer of iron and zinc called the ζ phase, which has a relatively low bonding strength.
[0019] The iron-based material that has formed the zinc layer and alloy layer is covered with flux or other measures to prevent oxidation of the joining surface, and then preheated to a temperature just above the melting point of the brass alloy (880°C) for 30 minutes or more (adjusted depending on the volume of the product), and molten high-strength brass alloy is poured in and welded. When molten brass alloy comes into contact with an alloy layer of iron and zinc, which has poor bonding properties, the zinc dissolves into the molten brass alloy, forming a porous iron base, and the brass alloy wets and penetrates, forming a composite in which the brass alloy is three-dimensionally interwoven with the iron. This composite is continuous with the deposited brass alloy, and therefore acts as a bonding layer to increase the adhesive strength of the deposited brass alloy.
[0020] On the other hand, the zinc layer on the surface of the ferrous material dissolves when it comes into contact with the molten brass alloy, and the solute concentration gradient at the joint interface becomes large. As a result, the film-like Fe-Si-Mn compound formed on the iron surface changes into the form of columnar crystals that solidify and grow toward the molten brass alloy. In addition, the surface of an iron-based material alloyed with zinc has less generation of non-uniform solidification nuclei, and the brass alloy and compounds remaining in the gaps between the sparsely grown columnar crystals form a complex, improving the brittleness of the compound layer. This increases the adhesive strength of the deposited brass alloy.
[0021] As the iron-based material used in the present invention, mild steel, carbon steel, alloy steel, spheroidal graphite cast iron, etc. can be appropriately used depending on the application.
[0022] <Example> Next, assuming application to the piston shoe shown in Figure 1, a joining evaluation was carried out by casting and welding high-strength brass to chrome-molybdenum steel. The samples used for cast welding were made by lathe-machining a φ45 mm inner diameter molten SCM440H round bar as an iron-based material, and then coating it with (1) a 50 μm thick molten zinc plating (molten Zn), (2) a 25 μm thick electrolytic zinc plating (electrolytic Zn), and as a comparative example, (3) a 15 μm thick electrolytic copper plating (electrolytic Cu). The electrogalvanized sample (2) was subjected to a heat treatment at 350 to 500°C.
[0023] The basin for each sample was filled with flux such as borax, and heated in a furnace at 910°C for 35 minutes to melt the flux. As shown in Figure 4, high-strength brass alloy 2a with the composition shown in Figure 5, which had been melted in a high-frequency melting furnace, was poured into iron-based material 1a using a ladle 5a. At the joining surface, the molten flux 4a is swept away and replaced with the high strength brass alloy without coming into contact with the air. After pouring the copper alloy, it was immediately cooled from the bottom with high-pressure air so that solidification proceeded in a directional direction from the joining surface into the molten metal. In the table of FIG. 5, Examples 1 to 5 are brass alloys that contain substantially no Al, and Example 6 is a brass alloy containing a reduced Pb content and 1.62% Al. Both are within the range set by the present invention, and the joints were close to those shown in FIG. 2(a). In contrast, Comparative Examples 7 and 10 were subjected to electrical Cu plating and had a joint structure similar to that shown in FIG. 2(b).
[0024] Evaluation after casting and welding was carried out by penetrant testing and shear strength testing. In the penetrant test, the specimen with the copper alloy welded was cut lengthwise, and the presence or absence of a flaw detection reaction (welding failure) at the joint interface was visually inspected according to the test method of JIS Z2343. The pass / fail judgement was based on the number of flaws less than 1.6 mm in length being three or less. In addition, for the shear strength test, the sample to which the copper alloy was welded was machined to obtain a test piece having a cross section of 5 mm square, and a die set shown in FIG. 6 was used to apply a load P between the fixed die 62 and the movable punch 61, and the load required to shear the joint interface was measured. The load was then divided by the cross-sectional area to obtain the shear strength. The evaluation results are summarized in FIG.
[0025] In Examples 1 to 6 in which the present invention was applied, all of the penetrant tests passed, and the shear strength was 120 N / mm 2 The above values were obtained. On the other hand, in Comparative Examples 7 to 10, the flaw detection reaction length at the joint interface was large, and in the shear test, the copper alloy peeled off with a very small force, so that the shear strength could not be obtained. [Explanation of symbols]
[0026] 1 Shoe body 2. High-strength brass alloy 3 First flow hole 4 Swash plate 5 Piston 12 Spherical part 21 Annular protrusion 31 Storage recess 32 Second flow hole 51 First end 61 Movable Punch 62 Fixed Die P load
Claims
1. The steel sheet has a main body made of an iron-based material, a Zn-Fe alloy layer formed on a surface of the main body, and a high-strength brass alloy layer bonded to the surface of the Zn-Fe alloy layer and having excellent wear resistance and seizure resistance, The high strength brass alloy contains, in mass %, Cu: 55.0 to 65.0%, Mn: 2.0 to 5.0%, Si: 0.5 to 2.0%, and further contains one or more of Al: 0.5 to 2.0%, Pb: 0.5 to 4.0%, Sn: 1.0% or less, and P: 0.1% or less, with the balance being Zn and unavoidable impurities. A composite sliding part characterized by containing.
2. A method for producing the composite sliding part according to claim 1, A method for manufacturing a composite sliding part, comprising the steps of: forming a Zn-Fe alloy layer on a surface of the iron-based material; and contacting the molten high-strength brass alloy thereon to dissolve zinc into the high-strength brass alloy.
3. 3. The method for producing a composite sliding part according to claim 2, wherein the step of forming the Zn-Fe based alloy layer comprises forming a zinc layer having a thickness of 15 μm or more on a surface of the iron based material by hot-dip galvanizing, thereby forming a Zn-Fe based alloy layer below the interface thereof.
4. 3. The method for producing a composite sliding part according to claim 2, wherein the step of forming the Zn—Fe based alloy layer comprises forming a zinc layer having a thickness of 15 μm or more on a surface of the iron based material, and then performing a heat treatment at 350 to 500° C. to form a Zn—Fe based alloy layer under the interface therebetween.
Citation Information
Patent Citations
JP1972018979U
JP1975034495A
Sliding material with flame sprayed film
JP1995048665A
Method for bonding molten metal and solid metal
JP1995124737A
Joining method of ferrous material and high tension brass alloy and composite material joined by the method
JP1999058034A